2009
DOI: 10.1038/nature08551
|View full text |Cite
|
Sign up to set email alerts
|

Rationally tuning the reduction potential of a single cupredoxin beyond the natural range

Abstract: Redox processes are at the heart of numerous functions in chemistry and biology, from long-range electron transfer (ET) in photosynthesis and respiration to catalysis in industrial and fuel cell research. Nature accomplishes these functions by employing only a limited number of redox-active agents. A long-standing issue in these fields is how redox potentials are fine-tuned over a broad range with little change to the redox-active site or ET properties. Resolving this issue will not only advance our fundamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
379
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 278 publications
(404 citation statements)
references
References 29 publications
25
379
0
Order By: Relevance
“…One possible explanation of the different ET rates is structural perturbation of the Cu-ligand interactions and thus in ET pathways of the different Az mutants. The observed 3D structures (25) and EXAFS data (SI Text) show minimal perturbation of the Cu-ligand distances or angles in the mutants compared with WT Az, which rule out this possibility as the main contributing factor in the variants studied here.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One possible explanation of the different ET rates is structural perturbation of the Cu-ligand interactions and thus in ET pathways of the different Az mutants. The observed 3D structures (25) and EXAFS data (SI Text) show minimal perturbation of the Cu-ligand distances or angles in the mutants compared with WT Az, which rule out this possibility as the main contributing factor in the variants studied here.…”
Section: Discussionmentioning
confidence: 98%
“…S5). The analysis indicates that the relative conformational freedom has increased, or the rigidity has decreased, particularly around the copper binding site (SI Text and Table S5) (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AsCBP1 encodes a cupredoxin superfamily protein. Proteins from this family function in oxidation homeostasis and electron transfer reactions, which are involved in photosynthesis, respiration, cell signaling, and numerous reactions of oxidases and reductases (Lu et al, 2004;Solomon et al, 2004;Dennison, 2005;Marshall et al, 2009).…”
Section: Osa-mir528 Putative Target Identification and Responses To Smentioning
confidence: 99%
“…In an earlier study, Marshall et al found that the redox potential of some metalloproteins changed when an amino acid close to the active site was replaced. 32 In Nii3-WT and Nii4-WT, Residue 448 is located close to the [4Fe-4S] cluster (Fig. 6).…”
Section: Function Of the Met175 Residue In Nii3-wtmentioning
confidence: 99%